Halal Marketing Approaches: A Systematic Review of Strategies, Challenges, and Social Implication - Yusran, Husna Leila; Masnita, Yolanda; Ali, Jati Kasuma; Jatunilawati, Yuana (AL-MUZARA'AH, 2025)
Halal, meaning "lawful and permitted," is deeply rooted in Islamic philosophy and teachings. Halal marketing refers to the strategies and approaches used to promote and sell products that comply with halal standards. This systematic review aims to examine the various marketing approaches utilized in promoting halal products. Some critics argue that the emphasis on halal products can lead to exclusion and division within societies, as it may prioritize catering to a specific religious group over others. They contend that promoting halal products exclusively may create a sense of segregation and hinder social integration. Utilizing the PRISMA method and analyzing publication from Scopus database. The study investigates diverse marketing technique used in promoting halal products. Several countries were included in this review, including Indonesia, Malaysia, Turkey, Arab Saudi, and the United Arab Emirates. The result of this review will provide insights into the marketing approaches that have been successful in promoting halal products and highlight any potential implications of these strategies on social integration. The finding suggest that halal marketing approaches vary across different countries, with a focus on building trust, emphasizing authenticity, and utilizing digital platforms. Based on the findings of this systematic review, it can be concluded that there are diverse marketing approaches used in promoting halal products. The study recommends future research explore of the impact of halal marketing on social integration and the potential for inclusive marketing strategies that can cater to a diverse consumer.